2017
DOI: 10.1002/chem.201704554
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,1′‐ and 2,2′‐Bicarbazole Alkaloids by Iron(III)‐Catalyzed Oxidative Coupling of 2‐ and 1‐Hydroxycarbazoles

Abstract: We describe the synthesis of 1,1'- and 2,2'-bicarbazoles by oxidative homocoupling of 2- and 1-hydroxycarbazoles. The oxidative coupling using catalytic amounts of F PcFe can be applied to both groups of substrates. Although F PcFe generally provides the best yields for the synthesis of 1,1'-bicarbazoles, di-tert-butyl peroxide affords better results for the 2,2'-bicarbazoles. In our study, we have achieved the first syntheses of the biscarbalexines A-C, bisglybomine B, 2,2'-dihydroxy-7,7'-dimethoxy-3,3'-dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 97 publications
0
40
0
1
Order By: Relevance
“…The oxidative products can be strongly affected by multiple substituents in the carbazole. In Fe III ‐catalyzed oxidations, C1−C1′ and C2−C2′ couplings are obtained if hydroxy and methyl substituents are introduced onto the carbazole . Furthermore, the synthesis of a high molecular‐weight polymer by oxidative polymerization of 1,4,5,8,9‐pentanmethylcarbazole with FeCl 3 in chloroform has been reported.…”
Section: Oxidative Reactions Of Carbazole and Its Derivativesmentioning
confidence: 99%
“…The oxidative products can be strongly affected by multiple substituents in the carbazole. In Fe III ‐catalyzed oxidations, C1−C1′ and C2−C2′ couplings are obtained if hydroxy and methyl substituents are introduced onto the carbazole . Furthermore, the synthesis of a high molecular‐weight polymer by oxidative polymerization of 1,4,5,8,9‐pentanmethylcarbazole with FeCl 3 in chloroform has been reported.…”
Section: Oxidative Reactions Of Carbazole and Its Derivativesmentioning
confidence: 99%
“…Then, we turned our attention to the projected iron-catalyzed oxidative homocoupling of 1-(diphenylamino)naphthalene (3). Recently, we applied our iron-catalyzed oxidative coupling methodology to the C-C homocoupling of diarylamines, 1-, and 2-hydroxycarbazoles, as well as to the cross coupling of tertiary anilines with hydroxyarenes [20][21][22]. Iron as a first-row transition metal is environmentally safe and has become a powerful tool in synthetic organic chemistry with many applications for selective C-H bond activation [23][24][25][26].…”
Section: Synthesismentioning
confidence: 99%
“…The oxidation of compound 3 with chloranil provides compound 4 only as the minor isomer in an inseparable mixture with the corresponding benzidine derivative [15]. Based on our previous studies [20][21][22], we envisaged to develop an iron-catalyzed homocoupling of the triarylamine 3 with air as the sole oxidant. Using catalytic amounts (2 mol%) of FePcF 16 and substoichiometric amounts (40 mol%) of methanesulfonic acid as an additive at room temperature provided N,N,N',N'-tetraphenylnaphthidine (4) in 48% yield along with the N,N,N',N'-tetraarylnaphthidine 5 as a by-product in 11% yield (Scheme 2).…”
Section: Synthesismentioning
confidence: 99%
“…In the same year, the Beifuss group generated a similar cyclic trimer from sesamol through laccase oxidation in 3 % yields (Scheme b) . Likewise, in 2018, it was found that methylcarbazoles are able to form spiroketal trimers, albeit in low yield (Scheme c) . The low yields in such processes likely arise from the selectivity challenges associated with phenol C−C dimerization in addition to two C−O bond‐forming reactions.…”
Section: Introductionmentioning
confidence: 99%